DAMPAK KEBERADAAN LIPPO PLAZA TERHADAP KINERJA LALU LINTAS DI RUAS JALAN VETERAN KOTA KUPANG - Bolla, Margareth E.; Udiana, I Made; Utama, Andi A.A.W. (Jurnal Teknik Sipil, 2017)
This research aimed at measuring level of performance in the form of service capacity at Veteran St., as it was affected by the existence of Lipo Plaza. The affect of the business center on service capacity of some sections of roads would be expressed in the comparisons of traffic volume, traffic capacity and degree of saturation (DS) before its existence, to the same after it had existed. Result of analysis in this research showed that there was a change in traffic volume, either increasing or decreasing. Increase of traffic volume occurred at segment of Veteran St., Patung Kirab area, Nostalgia Park area, Ina Bo’I, W.R. Monginsidi St., and Perintis Kemerdekaan St., each in value of 81.5 pmu/h, 35.97 pmu/h, 17.41 pmu/h, 8.83 pmu/h and 38.94 pmu/h respectively; whereas decrease of the same occurred at road segment to the back of Ruko Oebobo, in the value of 1.37 pmu/h. Service level of Veteran St. was proved to be still adequate despite the dercrease of DS at Veteran St., Patung Kirab area, Nostalgia Park area, Ina Boi, W.R. Monginsidi St, and Perintis Kemerdekaan St., each in the value of 4.05%, 2.07%, 0.75% 0.34% and 2.86 respectively. There was still location with decreasing DS that is the segment of road to the back of Ruko Oebobo, namely 0.13%. Observation also showed that there exists potency for traffic jam, therefore measures for prevention was recommended, such as installing warning traffic-light at intersection of Veteran St., Nostalia Park and Ruko Oebobo, and temporary road separator at Veteran St. These could as well prevent traffic crash at conflict points.